Une alliance singulière et durable : Les communistes néerlandais et la Ligue néomalthusienne (Nieuw-Malthusiaanse Bond, NMB), 1909-1940 - Elke Weesjes (Cahiers d’histoire.)
Based on a series of interviews with communists, communist archives, and a wide range of other sources, this article explores Dutch Communist Party’s stances on sexual health and sexuality, and discusses its affiliation with the Nieuw Malthusiaanse Bond (NMB, New-Malthusian League) in the period 1909-1940. It argues that Dutch communist views and practice deviated significantly from Soviet policy and guidelines in matters concerning sexuality and can be traced back to a powerful radical tradition rooted in anarchism and home-grown orthodox Marxism.